Sedimentary and tectonic evolution of a trench-slope basin in the Nankai subduction zone of southwest Japan - Underwood, M.; Moore, G.; Taira, A.; Klaus, A.; Wilson, Moyra; Fergusson, C.; Hirano, S.; Steurer, J. (SEPM - Soc Sedimentary Geology, 2003)
Leg 190 of the Ocean Drilling Program yielded discoveries about the early stages of tectonic and sedimentary evolution of atrench-slope basin in the Nankai subduction zone of southwest Japan. Lithofacies character, biostratigraphy, and seismic-reflection data show that the basin's architecture was constructed during the early Quaternary by frontal offscraping of coarse-grained trench-wedge deposits. Clast types in muddy gravel beds indicate that one of the trench's polymictic sources was enriched in low-grade meta sedimentary rocks. Outcrops of the Shimanto Belt on the island of Shikoku contain comparable lithologic assemblages, so we suggest that some of the turbidity currents and debris flows were funneled from that source through a transverse canyon-channel system.Offscraped trench deposits are mildly deformed and nearly flat lying beneath the slope basin. Bedding within the basin laps onto a hanging-wall anticline that formed above a major out-of-sequence thrust fault. Rapid uplift brought the substrate above the calcite compensation depth soon afterthe basin was created. The sediment delivery system probably was rerouted during subduction of the Kinan seamounts, thereby isolating the juvenile basin from coarse sediment influx. As a consequence, the upper 200 meters of basin fill consist of nanno fossil-rich hemipelagic mud with sparse beds of volcanic ash and thin silty turbidites. Intervals of stratal disruption are also common, and the soft-sediment folding resulted from north- to northeast-directed gravitational failure. The Nankai accretionary prism has grown 40 km in width during the past 1 My, and the slope basin is already filled to its sill point on the seawardside. The stratigraphy displays an upward fining and thinning trend, in contrast to the upward coarsening and thickening mega-sequences depicted by some conceptual models for slope basins.